2019
DOI: 10.1136/bmjspcare-2018-001739
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose ketamine adjuvant treatment for refractory pain in children, adolescents and young adults with cancer: a pilot study

Abstract: ObjectivesKetamine, an N-methyl-D-aspartate receptor antagonist, is effective at relieving adult cancer pain, although there have been very few reports to date regarding its use in children and in adolescents and young adults (AYA). This study assessed the efficacy, safety and opioid-sparing effects of low doses of ketamine added to opioid analgesics to alleviate persistent cancer pain.MethodsThis prospective, multicentre, observational trial collected data regarding demographics, pain characteristics, pain sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…Prior studies with LDKI in pediatric hematology/oncology patients (Table 1) have similarly struggled to define an objective response for multiple reasons: 1) studies were almost all retrospective; 2) patients with end-stage cancer had increasing pain due to their underlying condition; 3) patients' pain may have naturally improved over time and improvement unnecessarily attributed to LDKI initiation (i.e., regression to the mean); 4) multiple different measures were utilized to define which pre-LDKI and post-LDKI pain scores to compare; and 5) challenges of generalizing an intervention with significant inter-patient variability. The single recent multicenter prospective observational trial by Courade et al [9] in pediatric and young adult cancer patients reported meaningful benefit in pain scores when comparing the day of LDKI initiation and two days later. Given the rapid onset of action of LDKI, two days may or may not be an appropriate time frame to measure response.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies with LDKI in pediatric hematology/oncology patients (Table 1) have similarly struggled to define an objective response for multiple reasons: 1) studies were almost all retrospective; 2) patients with end-stage cancer had increasing pain due to their underlying condition; 3) patients' pain may have naturally improved over time and improvement unnecessarily attributed to LDKI initiation (i.e., regression to the mean); 4) multiple different measures were utilized to define which pre-LDKI and post-LDKI pain scores to compare; and 5) challenges of generalizing an intervention with significant inter-patient variability. The single recent multicenter prospective observational trial by Courade et al [9] in pediatric and young adult cancer patients reported meaningful benefit in pain scores when comparing the day of LDKI initiation and two days later. Given the rapid onset of action of LDKI, two days may or may not be an appropriate time frame to measure response.…”
Section: Discussionmentioning
confidence: 98%
“…Continuous intravenous infusions of lidocaine or ketamine have been used to treat pain that is refractory to opioids 13,14 . Lidocaine infusion, unfortunately, requires admission to the intensive care unit for continuous monitoring during drug initiation and dose titration due to risks of bradycardia, respiratory depression and seizure 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Courade et al . recently published a prospective multicentric trial to evaluate the efficacy of continuous infusion of low-dose ketamine through the course of three days as adjunctive therapy in 38 children and adolescents with persistent pain 14 . Most of the patients in this study were being treated palliatively for solid malignancies and 97% of them were already receiving intravenous morphine for pain management.…”
Section: Discussionmentioning
confidence: 99%
“…53 Low-dose ketamine infusion for refractory pain in children with cancer has been shown to significantly reduce pain. [54][55][56] In this regard, the antihyperalgesic and antiallodynic effect of ketamine has been mentioned. 57,58 Addition of IV ketamine for pain has also been seen to reduce the dose of opioids required.…”
Section: Cancer-related Painmentioning
confidence: 99%
“…In pediatric end‐of‐life care, ketamine patient‐controlled analgesia has been used successfully 53 . Low‐dose ketamine infusion for refractory pain in children with cancer has been shown to significantly reduce pain 54–56 . In this regard, the antihyperalgesic and antiallodynic effect of ketamine has been mentioned 57,58 .…”
Section: Scope Of Ketamine In Pediatric Oncologymentioning
confidence: 99%